Educational panacea to entrepreneurship: Interactive ENT300 videopreneur / Nur Fadhlina Zainal Abedin, Faridah Pardi and Asma' Rashidah Idris - Zainal Abedin, Nur Fadhlina; Pardi, Faridah; Idris, Asma' Rashidah (2021)
All undergraduate programme students at Universiti Teknologi MARA (UiTM), must undertake Fundamentals of Entrepreneurship (ENT300). However, concerns such as gender disparities in academic achievement have been a subject of controversy, particularly between technical and non- technical courses. We thereby investigate the possibility of disparity exists in this course for the selected samples in the UiTM Negeri Sembilan branch using an independent sample T-test. The findings reveal that female students outperformed male students in the ENT300 course. To reduce the gender gap performance in academic, interactive learning activities such as digital technology applications could be designed. Therefore, our goal is to create a dynamic learning platform that can accommodate various learning styles, including visual, auditory, and kinaesthetic. Hence, an Edupreneur Centre website is created to gather up all relevant materials, especially for ENT300 and entrepreneurship in general. This website serves as a one-stop center for students, instructors, and the public who are interested in entrepreneurship. This website is unique because there is no website available so far that is entirely applicable to the ENT300 modules.